PERUBAHAN SOSIAL EKONOMI MASYARAKAT SEKITAR DANAU PERINTIS - Hizran Patila; Rauf A Hatu; Sahrain Bumulo (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study examines the social and economic changes experienced by the communities surrounding Lake Perintis, located in Huluduotamo Village, Suwawa District, Bone Bolango Regency, as an impact of the rapid development of the tourism area. The research employs a descriptive qualitative approach, using data collection methods such as field observation, in-depth interviews, and documentation to obtain a comprehensive understanding of community conditions before and after the tourism development. The findings indicate that the development of Lake Perintis has brought positive impacts to the local community, including increased income, the creation of new job opportunities, and a shift in livelihoods from the agricultural sector to the service and tourism sectors. Furthermore, the development has stimulated the growth of small and medium enterprises based on the creative economy, strengthened social interaction among residents, and expanded access to new economic opportunities. However, the study also reveals several negative impacts, such as increased competition between local and migrant traders, concerns over environmental degradation caused by uncontrolled tourism activities, and inequality in business space management and profit distribution. Therefore, a sustainable and participatory tourism management strategy is required to ensure that the development of Lake Perintis not only enhances the community's economic well-being but also maintains social balance, cultural values, and environmental sustainability in the area.